TERPATRI (Forgiveness Therapy and Gayatri Mantra–Based Spiritual Intervention) on Resilience among Sexual Harassment Survivors: A Quasi-Experimental Study - Wardana, Ketut Eka Larasati; Juniantari , Putu Wahyu Sri (Journal of Applied Nursing and Health, 2026)
Background: Victims of sexual abuse often experience long-term psychological impacts such as trauma, emotional distress, and reduced resilience. Although various interventions exist, most focus on cognitive and behavioral approaches and lack integration of culturally relevant spiritual aspects. Therefore, this study evaluates the effectiveness of TERPATRI—an integration of forgiveness therapy and Gayatri Mantra spirituality—in improving resilience among victims of sexual abuse. Methods: This study used a pre-post quasi-experimental design with a control group. Participants were recruited using purposive sampling techniques, involving 64 victims of sexual abuse (32 in the intervention group and 32 in the control group). The inclusion criteria for this study were female victims of sexual abuse who were able to stand, open their mouths, hear, and communicate in Balinese and Indonesian. Meanwhile, the exclusion criteria for this study were victims of sexual abuse who had mental disorders, victims under the age of 5, and victims who were illiterate and did not have strong witnesses for this study. The main outcome variable was psychological resilience, which was measured using the Brief Resilience Scale (BRS). The analysis was performed using a paired t-test, with a significance level set at p < 0.05. Results: The intervention group showed a significant increase in resilience after participating in TERPATRI, with average scores increasing from pre-intervention to post-intervention. The paired t-test showed a statistically significant difference (p < 0.001), accompanied by a large effect size (Cohen's d > 0.80), indicating a substantial increase in resilience compared to the initial condition and the control group. Conclusion: TERPATRI has been proven effective in improving the resilience of sexual abuse victims. The integration of forgiveness therapy with Gayatri Mantra spirituality shows potential as a culturally and contextually sensitive mental health intervention, especially in communities with a strong spiritual background. This approach has the potential to be developed as a complementary intervention in psychological recovery services for victims of sexual violence.